Reverse altitudinal cline in cold hardiness among Erebia butterflies - Vrba, Pavel; Konvicka, Martin; Nedved, Oldrich (Cryo letters, 2012)
There is strong evidence for a shifting of range boundaries by many temperate butterfly species to higher altitudes and latitudes. Climate change represents a potential threat to mountain fauna. Nevertheless, information on ecophysiological limits of individual species is scarce. We studied the lower thermal limits of four species representing the prevailingly mountain Holarctic butterfly genus Erebia. We measured the cold tolerance of hibernating larvae, namely the supercooling point (SCP) and the lower lethal temperature (LLT). Three mountain species were freeze avoiding, with various levels of SCP (-8 to -22 degree C), and LLT close to SCP. The only exception was lowland E. medusa, whose caterpillars were freeze tolerant with LLT (-21 degree C) slightly below its SCP (-17 degree C). Surprisingly, LLT was highest in the alpine E. tyndarus and lowest in E. medusa inhabiting lower altitudes with higher mean winter temperatures. We explain the observed reversed altitudinal cline in cold hardiness by the buffering function of snow cover in the hibernacula of caterpillars that is strong at high mountains but irregular, unpredictable and thus unreliable in lowlands.
Keywords: klimatické změny; Snow; aklimatizace; Female; Larva; nízká teplota; hibernace; Animals; motýli; ženské pohlaví; Acclimatization; Butterflies; Climate Change; sníh; Hibernation; zvířata; Cold Temperature; larva